Biodegradable resin composition and film made thereof

By using polyester materials with high relative biodegradation rates, combined with the control of intrinsic viscosity and heat-wet treatment conditions, the problem of slow degradation of existing biodegradable plastics in household compost or soil is solved, and stable thickness and excellent mechanical properties are ensured when preparing the film, achieving rapid biodegradation and film preparation suitable for food packaging.

JP7647764B2Active Publication Date: 2025-03-18TORAY INDUSTRIES INC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2022550919
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-11-18
Filing Date
2021-03-19
Publication Date
2025-03-18
Estimated Expiration
2041-03-19

AI Technical Summary

Technical Problem

Existing biodegradable plastics degrade slowly in household compost or soil, and when preparing plastic films, the processing stability, mechanical properties and thermal properties are insufficient, making it difficult to produce films with stable thickness and biaxial tensile properties.

Method used

Polyester materials with high relative biodegradation rates are used, specifically including one or more acetates, aromatic acetates and carbonate polymers, and the intrinsic viscosity and thermal and moisture treatment conditions of the polymer are controlled during the treatment process to achieve rapid biodegradation and good mechanical properties.

Benefits of technology

It realizes rapid degradation of biodegradable plastics in household compost or soil, and ensures stable thickness and excellent mechanical properties when preparing films. It is suitable for food packaging and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007647764000001
    Figure 0007647764000001
  • Figure 0007647764000002
    Figure 0007647764000002
  • Figure 0007647764000003
    Figure 0007647764000003
Patent Text Reader

Abstract

The present invention provides a biodegradable resin having an intrinsic viscosity of 1.0 dL / g or greater and exhibiting a loss in intrinsic viscosity of 10% or greater after 6 hours at 70°C and 85% RH. The present invention also provides a biodegradable resin containing 70% or greater by weight of polylactic acid, which exhibits a relative biodegradation rate of 90% or greater within 12 months when evaluated for degradability by home composting at 28°C according to the conditions specified in ASTM D5338-15. The biodegradable resin of the present invention combines rapid biodegradability with storage stability, and also exhibits excellent mechanical, optical, and barrier properties. It can be used for a wide range of applications, including packaging and courier transport. After its useful life, it rapidly biodegrades into small molecules such as carbon dioxide and water, thereby not polluting the environment. The present invention also provides a biodegradable resin film and a product thereof using the biodegradable resin, as well as a multilayer film and a product thereof containing the biodegradable resin film.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polymeric material field, and more particularly to a biodegradable resin. composition And biodegradable resin made of the same composition Concerning film. [Background technology]

[0002] Plastics are important materials that are used in many aspects of human production and life, but many plastics remain in the environment for long periods after their end of life and can lead to pollution if not treated.

[0003] Biodegradable plastics are decomposed by bacteria, and the above problems can be effectively solved by using these materials. Currently, the raw materials for biodegradable plastics available on the market include polylactic acid, polybutylene terephthalate adipate, polyhydroxyalkanoate, polybutylene succinate, polyglycolic acid, polycaprolactone, polypropylene carbonate, etc. Polylactic acid is one of the most widely used biodegradable plastics at present, due to its excellent overall characteristics of processability and mechanical properties. However, like other various resins, polylactic acid also has certain disadvantages when used for various applications. For example, polylactic acid has a slow biodegradation rate, especially in environments with low bacterial content and low environmental temperatures. That is, polylactic acid is certified as compostable when certified based on the standard method for industrial composting, but is not certified as compostable by standard methods such as the home composting method and the soil burial method. This means that it does not decompose quickly under home composting conditions or after burial in soil, but remains in the compost or soil for an extended period of time.

[0004] On the other hand, polymers that biodegrade relatively quickly, such as polyhydroxyalkanoates, polyglycolic acids, and polycaprolactones, are considered to be biodegradable by the standard methods prescribed in the industrial composting method, the home composting method, and the soil burial method, but the processability and usability of these materials are unsatisfactory. In particular, when these materials are required to be used as plastic films, they always show insufficient properties such as processing stability, viscoelasticity, and thermal properties, making it difficult to manufacture films with stable thickness and properties, especially biaxially stretched films. In addition, these materials are also insufficient in terms of usability, such as strength, barrier properties, heat resistance, and heat sealability. Summary of the Invention [Problem to be solved by the invention]

[0005] Therefore, there is a demand for a biodegradable resin that can decompose quickly even after being buried in soil under home composting conditions, does not remain in compost or soil for long periods of time, can be used to produce a stable film with excellent properties, and has a high biodegradation rate that can be applied to fields such as food packaging. [Means for solving the problem]

[0006] In order to solve the above problems, the present invention provides a polyester resin having an intrinsic viscosity of 1.0 dL / g or more and an intrinsic viscosity loss rate of 10% or more after treatment at 70° C. and 85% RH for 6 hours. And the intrinsic viscosity loss rate after treatment for 6 hours at 50°C and 85% RH is 10% or less. biodegradable resin composition to provide. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] The biodegradable resin composition In the general sense, it means a polymer composition that is considered to have biodegradability, and in particular, it means a polymer composition that has a relative biodegradation rate of 90% or more after 6 months when the biodegradability is evaluated according to the conditions specified in GB / T 19277.1-2011. Here, the relative biodegradation rate is the percentage of the biodegradation rate of the sample to the biodegradation rate of the control material. Assuming that the above definition is satisfied, biodegradable resin compositionmay contain one or more of aliphatic polyesters, aliphatic aromatic polyesters, and aliphatic polycarbonates, and may further contain one or more selected from the group consisting of polylactic acid, polybutylene terephthalate adipate, polyhydroxyalkanoate, polybutylene succinate, polyglycolic acid, polycaprolactone, polypropylene carbonate, and copolymers of the above polymers.

[0008] The intrinsic viscosity (IV) was measured by dissolving a sample in chloroform, removing insoluble matters, preparing a 3±1 mg / mL solution, and measuring the solution at 30° C. using an Ubbelohde viscometer. The intrinsic viscosity can be used to characterize the molecular weight of a biodegradable resin. If the intrinsic viscosity is less than 1.0 dL / g, the molecular weight of the resin is low, and the usability such as processability, mechanical properties, and thermal properties may be insufficient. Therefore, the biodegradable resin according to the present invention composition Typically, the biodegradable resin according to the present invention has a characteristic viscosity of 1.0 dL / g or more. composition has a characteristic viscosity of 1.2 dL / g or greater.

[0009] Furthermore, the biodegradable resin according to the present invention composition The intrinsic viscosity loss rate after treatment at 70°C and 85% RH for 6 hours is 10% or more, preferably 18% or more, and more preferably 25% or more. composition has a fast biodegradation rate.

[0010] Furthermore, the biodegradable resin according to the present invention composition The biodegradable resin has an intrinsic viscosity loss rate of 10% or less, preferably 6% or less, after treatment at 50°C and 85% RH for 6 hours. composition For biodegradable resins, a fast biodegradation rate is required. compositionHowever, it is also required that the biodegradable polyester maintains excellent usability before the end of its life, i.e., has excellent storage stability. The present inventors have found that a biodegradable polyester having an intrinsic viscosity loss rate of 10% or less, preferably an intrinsic viscosity loss rate of 6% or less, after treatment at 50°C and 85% RH for 6 hours can provide the above storage stability.

[0011] Furthermore, in order to improve the biodegradation rate, the biodegradable resin composition has a content of 0.1×10 -4 mol / g or more of carboxyl groups, preferably with a content of 0.1×10 -4 ~10×10 -4 mol / g of carboxyl groups. The carboxyl groups are biodegradable resins. composition The polymer may be present in the biodegradable resin. composition Carboxylic acid groups may be present in low molecular weight or oligomers. If there are too few carboxylic acid groups, the biodegradation rate will not increase significantly. Conversely, if there are too many carboxylic acid groups, it may be difficult to satisfy usability such as processability, mechanical properties, thermal properties, and storage stability.

[0012] Furthermore, the biodegradable resin according to the present invention composition contains 70% by weight or more of polylactic acid. The polylactic acid is one or more of homopolymers or copolymers of lactic acid. Polylactic acid can be obtained by dehydration condensation of a raw material such as lactic acid, but can also be obtained by ring-opening polymerization of a raw material such as lactide. Examples of lactide include L-lactide, which is a cyclic dimer of L-lactic acid, D-lactide, which is a cyclic dimer of D-lactic acid, meso-lactide obtained by cyclic dimerization of D-lactic acid and L-lactic acid, and DL-lactide, which is a racemic mixture of D-lactide and L-lactide. In the present invention, any of the above lactides can be used. The copolymer of lactic acid contains lactic acid copolymerization units and non-lactic acid copolymerization units as copolymerization units, and preferably contains 85 to 99 mol% of L-lactic acid and / or D-lactic acid copolymerization units. The non-lactic acid copolymerized units are preferably one or more of hydroxybutyric acid, hydroxypentanoic acid, hydroxycaproic acid, hydroxyoctanoic acid, glycolide, and caprolactone.

[0013] The biodegradable resin composition By containing 70% by weight or more of polylactic acid, it is useful for improving usability such as processability, mechanical properties, thermal properties, etc. More preferably, it contains 80% by weight or more of polylactic acid, and even more preferably, it contains 85% by weight or more of polylactic acid.

[0014] Furthermore, from the viewpoint of improving usability such as processability, mechanical properties, and thermal properties, and storage stability, the number average molecular weight of the polylactic acid is preferably 50,000 or more, and more preferably 80,000 or more.

[0015] Furthermore, from the viewpoint of improving properties such as biodegradability, processability, and mechanical properties, the optical purity of the polylactic acid is preferably 83 to 96%, more preferably 86 to 90%. The optical purity is the ratio of the specific rotation of a compound to the specific rotation of a standard control product, and in the case of polylactic acid, it is the ratio of the specific rotation of a sample to the specific rotation of L-polylactic acid (-156°). The optical purity of polylactic acid can be controlled by adjusting the content of L-lactic acid units and D-lactic acid units constituting the polylactic acid segment, or more simply, by using two or more polylactic acids with different contents of D-lactic acid units in combination. For example, polylactic acid with different optical purities can be obtained by using polylactic acid with an optical purity of 97% or more and polylactic acid with an optical purity of 96% or less in combination at a predetermined weight ratio. Preferably, the blending ratio of the polylactic acid with an optical purity of 97% or more and the polylactic acid with an optical purity of 96% or less is 40:60 to 90:10. The optical purity can be measured with an accuracy of 1% using a polarimeter. The optical purity measured by the above measurement method is expressed with an accuracy of 1%. That is, polylactic acid with an optical purity of 97% or more means polylactic acid with an optical purity of 97%, 98% or higher as measured by the above measurement method, and polylactic acid with an optical purity of 96% or less means polylactic acid with an optical purity of 96%, 95% or lower as measured by the above measurement method.

[0016] Furthermore, from the viewpoint of improving properties such as biodegradability, processability, and mechanical properties, the fusion enthalpy of the polylactic acid is preferably 10 to 58 J / g, more preferably 20 to 35 J / g. If the fusion enthalpy of the polylactic acid is less than 10 J / g, the processability and mechanical properties of the polylactic acid are deteriorated. If the fusion enthalpy of the polylactic acid is more than 42 J / g, the biodegradation rate is too slow.

[0017] Furthermore, from the viewpoint of improving properties such as biodegradability, processability, and mechanical properties, the biodegradable resin is preferably composition The cold crystallization temperature in the second heating step is between 120°C and 135°C.

[0018] The enthalpy of fusion and the cold crystallization temperature of the second heating are measured by differential scanning calorimetry.

[0019] Furthermore, in order to improve the biodegradation rate, the biodegradable resin composition contains a compound having at least one of a carboxyl group, an acid anhydride group, a sulfonic acid group, a hydroxyl group, and an amine group, and the content of the compound is 0.1 to 10% by weight. composition The biodegradable resin contains 0.1 to 5% by weight of the compound. composition contains 0.1 to 10% by weight of a carboxylic acid and / or a carboxylic acid anhydride, and more preferably, the biodegradable resin composition contains 0.1 to 5% by weight of carboxylic acid and / or carboxylic acid anhydride.

[0020] Carboxylic acids are organic compounds having a carboxyl group. Examples of the carboxylic acid include monobasic acids such as acetic acid, butyric acid, and stearic acid, dibasic acids such as succinic acid, adipic acid, and sebacic acid, and polybasic acids such as citric acid. Examples of the carboxylic acid include saturated carboxylic acids such as lauric acid, myristic acid, and palmitic acid, and unsaturated carboxylic acids such as oleic acid, docosahexaenoic acid, and maleic acid.

[0021] Carboxylic acid anhydrides are organic compounds that contain an acid anhydride group. Examples include saturated carboxylic acid anhydrides such as succinic anhydride, glutaric anhydride, and n-caproic anhydride, and unsaturated carboxylic acid anhydrides such as crotonic anhydride and maleic anhydride.

[0022] If the amount of carboxylic acid and / or carboxylic anhydride is too small, the effect of improving the biodegradation rate is not clear. If the amount of carboxylic acid and / or carboxylic anhydride is too large, the biodegradable resin composition This leads to a significant decrease in usability, such as processability, mechanical properties, thermal properties, and storage stability.

[0023] Further, the number of carbon atoms of the carboxylic acid and / or carboxylic anhydride is 4 or more. More preferably, the carboxylic acid is succinic acid, 2-methyl-2-hydroxysuccinic acid, propylsuccinic acid, glutaric acid, 2-methyl-glutaric acid, 3-methyl-glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, dodecanedioic acid, galactaric acid, citric acid, cyclohexanecarboxylic acid, benzoic acid, naphthalenecarboxylic acid, tetrahydroxysuccinic acid, tetramethylsuccinic acid, aminopentanoic acid, heptanoic acid, isoheptanoic acid, octanoic acid, aminooctanoic acid, isooctanoic acid, nonanoic acid, aminononanoic acid, decanoic acid, undecanoic acid, dodecanoic acid, tridecanoic acid, tetradecanoic acid, pentadecanoic acid, hexadecano ... and the carboxylic acid anhydride is one or more of hexanoic anhydride, salicylic anhydride, pentanoic anhydride, octanoic anhydride, heptanoic anhydride, succinic anhydride, glutaric anhydride, benzoic anhydride, maleic anhydride, phenoxyacetic anhydride, phthalic anhydride, polysebacic anhydride, and maleic anhydride-containing polymers.

[0024] The present inventors have discovered that by incorporating an appropriate amount of such a carboxylic acid and / or carboxylic anhydride, it is possible to obtain a biodegradable resin while effectively maintaining usability such as processability, mechanical properties, and thermal properties, and storage stability. composition It has been found that the biodegradation rate of

[0025] Furthermore, the biodegradable resin composition contains two or more carboxylic acids, or contains one or more carboxylic acids and one or more carboxylic acid anhydrides. composition contains sebacic acid and adipic acid, or sebacic acid and glutaric anhydride. The present inventors have found that combinations of these carboxylic acids and / or carboxylic anhydrides are effective in producing biodegradable resins. composition It has been found that this is particularly advantageous in improving the biodegradation rate of the composition, while effectively maintaining usability and storage stability, such as processability, mechanical properties, and thermal properties.

[0026] Furthermore, in order to improve the biodegradation rate and the properties such as flexibility, elongation, and thickness deviation of the film product, it is preferable to use the biodegradable resin. composition The biodegradable resin contains one or more of aliphatic polyesters other than polylactic acid, aliphatic-aromatic copolymer esters, and aliphatic polycarbonates. composition contains 5 to 50% by weight of one or more of aliphatic polyesters other than polylactic acid, aliphatic-aromatic copolymer esters, and aliphatic polycarbonates, and more preferably contains 10 to 30% by weight of one or more of aliphatic polyesters other than polylactic acid, aliphatic-aromatic copolymer esters, and aliphatic polycarbonates.

[0027] Preferably, the biodegradable resin compositioncontains 5 to 50% by weight of one or more of polycaprolactone, polybutylene succinate, polybutylene succinate adipate, polybutylene terephthalate adipate, polyhydroxyalkanoate, polypropylene carbonate, polyglycolic acid, copolymers of these polymers, and derivatives, and more preferably contains 10 to 30% by weight of one or more of polycaprolactone, polybutylene succinate, polybutylene succinate adipate, polybutylene terephthalate adipate, polyhydroxyalkanoate, polypropylene carbonate, polyglycolic acid, copolymers of these polymers, and derivatives.

[0028] The polycaprolactone (PCL) is a polymer containing -OCO(CH2)5- repeating units, and is usually a polymer obtained by ring-opening polymerization of caprolactone monomers. The polybutylene succinate (PBS) is a polymer of succinic acid and butylene glycol. The polybutylene succinate adipate (PBSA) is a polymer of succinic acid, adipic acid, and butylene glycol. The polybutylene terephthalate adipate (PBAT) is a polymer of adipic acid, terephthalic acid, and butylene glycol. The polyhydroxyalkanoate (PHA) is a polymer of -O-CHR-(CH2) m It is a polymer containing -CO- repeating units (where R is an alkyl group and m is an integer of 1 or more), and is usually a linear polyester produced by bacterial fermentation from natural edible sugars or lipids, such as poly 3-hydroxybutyrate, poly 3-hydroxyvalerate, poly 3-hydroxyoctanoate, poly 3-hydroxydodecanoate, and copolymers thereof. The polypropylene carbonate (PPC) is a polymer containing -CH2CHCH3OCOO- repeating units, and is usually synthesized using carbon dioxide and propylene oxide as raw materials. The polyglycolic acid (PGA) is a polymer containing -CH2COO- repeating units, and is usually synthesized from glycolic acid or glycolide, and is also called polyhydroxyacetate or polyglycolide.

[0029] Furthermore, in order to improve the biodegradation rate and mechanical properties such as flexibility, the biodegradable resin composition contains 50 to 500 ppm of a metal element. Furthermore, the metal element is one or more of sodium, magnesium, aluminum, potassium, calcium, barium, zinc, iron, copper, and tin. The presence of a metal element is advantageous for reactions such as ester exchange and chain extension between the polylactic acid and other resins or additives, and can increase compatibility.

[0030] Furthermore, the biodegradable resin composition contains a dispersed phase, and the average diameter of the dispersed phase is 0.5 to 6.0 μm.

[0031] The biodegradable resin according to the present invention composition In the above, one or more additives such as a filler, a plasticizer, a compatibilizer, an end-capping agent, a flame retardant, a nucleating agent, an antioxidant, a lubricant, an antistatic agent, an anti-fogging agent, a light stabilizer, an ultraviolet absorber, a pigment, an anti-mold agent, an antibacterial agent, or a foaming agent may be used, as long as the object of the present invention is not hindered.

[0032] The filler may be a fibrous, flake, granular or powdery filler commonly used in the rubber and plastics field, and may be an inorganic or organic filler. Specific examples of the inorganic filler include glass fiber, asbestos fiber, carbon fiber, graphite fiber, metal fiber, potassium titanate whisker, aluminum borate whisker, magnesium whisker, silicon whisker, wollastonite, sepiolite, asbestos, slag fiber, tobermorite, silica apatite, gypsum fiber, silica fiber, silica / alumina fiber, zirconia fiber, boron nitride fiber, silicon nitride fiber, and boron fiber, and may be one or more of fibrous inorganic fillers such as glass flakes, Examples of the filler include one or more of the following inorganic fillers in the form of flakes or particles: sulphuric acid, non-swelling mica, swelling mica, graphite, metal foil, ceramic beads, talc, clay, mica, sericite, zeolite, bentonite, vermiculite, montmorillonite, dolomite, kaolin, finely powdered silicic acid, feldspar powder, potassium titanate, fine hollow glass spheres, calcium carbonate, magnesium carbonate, calcium sulfate, titanium dioxide, boehmite alumina, silica, gypsum, uniformly dense quartz rock, dawsonite or white clay. The organic filler specifically includes one or more of the following organic synthetic fibers: starch, cellulose, vegetable fibers such as hemp fiber or bamboo fiber, animal fibers such as wool fiber, and organic synthetic fibers such as aramid fiber or aromatic polyester fiber. The filler can be subjected to any form of surface treatment to improve the interfacial adhesion with the resin.

[0033] The plasticizer is not particularly limited, and examples thereof include hydroxyl benzoate esters such as 2-ethylhexyl hydroxyl benzoate, polyhydric alcohol esters such as acetate ester of ethylene oxide adduct of glycerin, phthalate esters such as di-2-ethylhexyl phthalate, adipic acid esters such as dioctyl adipate, maleic acid esters such as di-n-butyl maleate, citric acid esters such as acetyl tributyl citrate, alkyl phosphate esters such as tricresyl phosphate, tricarboxylic acid esters such as trioctyl trimellitate, esters of succinic acid and triethylene glycol monomethyl ether, esters of adipic acid and diethylene glycol monomethyl ether, and the like. Examples of the polyoxyethylene alkyl ether include acetylated polyoxyethylene hexyl ether and other alkyl ether esters of polyvalent carboxylic acids, such as esters of 1,3,6-hexanetricarboxylic acid and polyethylene glycol monomethyl ether, acetylated polyoxyethylene alkyl (alkyl carbon number: 2 to 15) ethers such as acetylated polyoxyethylene hexyl ether, polyethylene glycol diacetates having an added mole number of ethylene oxide of 3 to 20, polyethylene oxide-1,4-butylene glycol ether diacetate, polyethylene glycol, polypropylene glycol, polyethers of polyethylene glycol-polypropylene glycol polymers, fats and oils such as soybean oil and olive oil, and polymers of the above chemical structures with polylactic acid. Preferably, the plasticizer is one or more of dioctyl phthalate, dibutyl phthalate, butyl benzyl phthalate, dioctyl sebacate, dibutyl sebacate, tributyl citrate, triethyl citrate, acetyl triethyl citrate, acetyl tributyl citrate, glycerin triacetate, polyethylene glycol, polypropylene glycol, polyethylene glycol-polypropylene glycol copolymer, polylactic acid-ethylene glycol copolymer, polylactic acid-propylene glycol copolymer, soybean oil, or epoxy soybean oil. The above plasticizers may be used alone or in combination of two or more.

[0034] The compatibilizer may be a compound containing one or more of an epoxy functional group, an isocyanate functional group, a carbodiimide functional group, an acid anhydride functional group, a silane functional group, an oxazoline functional group, or a phosphite functional group, and the total number of the functional groups contained in the compound is 2 or more.Specific examples of the compatibilizer include tolylene diisocyanate, diphenylmethane diisocyanate, p-xylylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, lysine triisocyanate, γ-glycidyloxypropyltrimethoxysilane, polycarbodiimide, ethylene-acrylate-maleic anhydride terpolymer, or an acrylate polymer having an epoxy functional group.

[0035] The end-capping agent includes a compound containing one of an epoxy functional group, an isocyanate functional group, a carbodiimide functional group, an acid anhydride functional group, a silane functional group, an oxazoline functional group, or a phosphite functional group, and the total number of the functional groups contained in the compound is one.

[0036] Furthermore, from the viewpoint of environmental protection, the biodegradable resin composition The biomass degree is preferably 70%, more preferably 80% or more, and further preferably 90% or more.

[0037] Further, preferably, the biodegradable resin composition When decomposition is evaluated by home composting at 28°C according to the conditions specified in ASTM D5338-15, the relative biodegradability of this substance is 90% or more within 12 months.

[0038] Further, preferably, the biodegradable resin composition When soil decomposition is evaluated according to the conditions specified in ASTM D5988-18, the biodegradation rate of is 90% or more within 24 months.

[0039] The present invention further provides a biodegradable resin that contains 70% by weight or more of polylactic acid and has a relative biodegradability of 90% or more within 12 months when the decomposition rate is evaluated by home composting at 28°C according to the conditions specified in ASTM D5338-15. composition to provide.

[0040] Furthermore, the biodegradable resin according to the present invention composition The intrinsic viscosity of the copolymer is preferably 1.0 dL / g or more, and more preferably 1.2 dL / g or more.

[0041] Further, preferably, the biodegradable resin according to the present invention is composition The intrinsic viscosity loss rate after treatment for 6 hours at 70°C and 85% RH is 18% or more.

[0042] Further, preferably, the biodegradable resin according to the present invention is composition The intrinsic viscosity loss rate after treatment at 50° C. and 85% RH for 6 hours is 10% or less, and more preferably 6% or less.

[0043] Further, preferably, the biodegradable resin according to the present invention is composition has a content of 0.1×10 -4 mol / g or more of carboxyl groups, and more preferably the content is 0.1×10 -4 ~10×10 -4 mol / g of carboxyl groups.

[0044] Further, preferably, the biodegradable resin according to the present invention is composition contains 80% by weight or more of polylactic acid.

[0045] Further, preferably, the biodegradable resin according to the present invention is composition The number average molecular weight of the polylactic acid is 50,000 or more.

[0046] Further, preferably, the biodegradable resin according to the present invention is composition The optical purity of the polylactic acid is 83 to 96%.

[0047] Further, preferably, the biodegradable resin according to the present invention is composition The melting enthalpy of polylactic acid is preferably 10 to 58 J / g, and more preferably 20 to 35 J / g.

[0048] Further, preferably, the biodegradable resin according to the present invention is composition The cold crystallization temperature in the second heating step is between 120°C and 135°C.

[0049] Further, preferably, the biodegradable resin according to the present invention is composition contains a compound having at least one of a carboxyl group, an acid anhydride group, a sulfonic acid group, a hydroxyl group, and an amine group, and the content of the compound is 0.1 to 10% by weight.

[0050] Further, preferably, the biodegradable resin according to the present invention is composition contains a carboxylic acid and / or a carboxylic anhydride, and the content of the carboxylic acid and / or the carboxylic anhydride is 0.1 to 10% by weight.

[0051] Further, the carboxylic acid and / or carboxylic acid anhydride preferably has 4 or more carbon atoms.

[0052] Furthermore, preferably, the carboxylic acid is one or more of succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, cyclohexanecarboxylic acid, benzoic acid, and naphthalenecarboxylic acid, and the carboxylic acid anhydride is one or more of succinic anhydride, glutaric anhydride, benzoic anhydride, maleic anhydride, phenoxyacetic anhydride, phthalic anhydride, polysebacic anhydride, and maleic anhydride-containing polymers.

[0053] Further, preferably, the biodegradable resin according to the present invention is compositioncontains 5 to 50% by weight of one or more of polycaprolactone, polybutylene succinate, polybutylene succinate adipate, polybutylene terephthalate adipate, polyhydroxyalkanoate, polypropylene carbonate, polyglycolic acid, or copolymers or derivatives of these polymers.

[0054] Further, preferably, the biodegradable resin according to the present invention is composition contains 50 to 500 ppm of metal elements.

[0055] Furthermore, the metal element is one or more of sodium, magnesium, aluminum, potassium, calcium, barium, zinc, iron, copper, and tin.

[0056] Further, preferably, the biodegradable resin according to the present invention is composition It contains a dispersed phase, and the average diameter of the dispersed phase is 0.5 to 6.0 μm.

[0057] The present invention further relates to the biodegradable resin. composition A biodegradable resin comprising composition Provide the film.

[0058] The biodegradable resin composition The film is made of the above-mentioned biodegradable resin. composition The raw material may be used to produce the polyester film by a known molding method such as extrusion, casting, pressing, inflation, calendaring, uniaxial stretching, or biaxial stretching, and may further be subjected to a heat treatment.

[0059] The biodegradable resin composition The thickness of the film is not particularly limited, but is generally from 1 μm to 5 mm.

[0060] Furthermore, the biodegradable resin compositionThe film is oriented in at least one of MD (length direction) or TD (width direction) to improve mechanical properties and production efficiency. The orientation can be achieved by uniaxial or biaxial stretching. In the case of biaxial stretching, the stretching ratios in the two directions (MD and TD) of the film may be the same or different. The polarized Raman spectrum of the film has a certain characteristic peak, and the peak intensity is related to the degree of orientation of the film. For a film containing polylactic acid, the 873 cm -1 (The peak value is denoted as P) and 1769 cm -1 The peak at (the peak value is written as Q) is considered to be a characteristic peak, and it can be judged whether or not the film is oriented by the following method. Polarized Raman spectrum measurement is performed on the cross section of the sample film, and P and Q in the film's length direction (MD), width direction (TD) and thickness direction (ZD) are obtained, and the P / Q values ​​in the three directions are calculated, (P / Q) MD , (P / Q) TD , (P / Q) ZD And then (P / Q) MD / (P / Q) ZD and (P / Q) TD / (P / Q) ZD The value is calculated. The measurement is repeated five times by the above method, and in each measurement, the measurement points are separated by 200 μm, and the direction of the measurement points is arbitrary. (P / Q) MD / (P / Q) ZD and (P / Q) TD / (P / Q) ZD If a certain average value is 1.1 or more, the film is oriented in that direction.

[0061] Furthermore, the degree of orientation in MD / ZD and / or TD / ZD is preferably 170% or more.

[0062] In addition, for the purpose of improving printability, lamination suitability, coating suitability, etc., the biodegradable resin according to the present invention is composition The film may further be subjected to various surface treatments, such as corona discharge treatment, plasma treatment, flame treatment, acid treatment, and release treatment.

[0063] Furthermore, the biodegradable resin composition In order to improve the transparency of the film, the biodegradable resin composition The total light transmittance of the film is 90% or more, and / or the haze is 40% or less, and / or the internal haze is 8% or less. composition The film has a total light transmittance of 90% or more, a haze of 40% or less, and an internal haze of 20% or less, more preferably a total light transmittance of 90% or more, a haze of 33% or less, and an internal haze of 11% or less.

[0064] Furthermore, the biodegradable resin composition The film contains a dispersed phase, and the aspect ratio of the dispersed phase in the MD / ZD plane and / or the TD / ZD plane is 1.5 or more, preferably 2.0 or more. The aspect ratio can be achieved by appropriately selecting the film preparation conditions such as the components and the orientation (uniaxial or biaxial stretching).

[0065] Furthermore, in order to improve the smoothness during use and the barrier properties due to a synergistic effect with the vapor deposition layer when used as a barrier packaging material, the biodegradable resin composition The film has a surface roughness of 0.05 to 0.5 μm on at least one side.

[0066] In order to improve smoothness, reduce surface roughness, reduce thickness deviation, and improve flexibility and elongation, it is preferable to use the biodegradable resin. compositioncontains 5 to 50% by weight of one or more of polycaprolactone, polybutylene succinate, polybutylene succinate adipate, polybutylene terephthalate adipate, polyhydroxyalkanoate, polypropylene carbonate, or copolymers of these polymers or derivatives. More preferably, contains 10 to 30% by weight of one or more of polycaprolactone, polybutylene succinate, polybutylene succinate adipate, polybutylene terephthalate adipate, polyhydroxyalkanoate, polypropylene carbonate, or copolymers of these polymers or derivatives. Even more preferably, contains 10 to 30% by weight of one or more of polycaprolactone, polybutylene succinate, polybutylene succinate adipate, polybutylene terephthalate adipate, or copolymers of these polymers or derivatives. In order to achieve the above-mentioned preferred aspect ratios of the dispersed phase in the MD / ZD plane and / or the TD / ZD plane, it is most preferable that the biodegradable resin composition The polycaprolactone content is 10 to 30% by weight.

[0067] Furthermore, in order to improve uniformity in usability such as mechanical properties, the biodegradable resin composition The film has a thickness variation coefficient of 10% or less. The thickness variation coefficient is the ratio of the standard deviation of the thickness to the average thickness. By appropriately selecting the components, the biodegradable resin composition The film thickness variation coefficient can be 10% or less. composition This can be achieved by incorporating 10 to 30% by weight of polycaprolactone in the polymer.

[0068] Furthermore, in order to improve usability, the biodegradable resin composition The film has a tensile strength of 60 MPa or more, a breaking elongation of 20% or more, and a tensile modulus of 4500 MPa or less, and preferably has a tensile strength of 70 MPa or more, a breaking elongation of 100% or more, and a tensile modulus of 3000 MPa or less.

[0069] Furthermore, the biodegradable resin composition When the film is evaluated for decomposition by home composting at 28°C according to the conditions specified in ASTM D5338-15, the relative biodegradability is 90% or more within 12 months.

[0070] Furthermore, the biodegradable resin composition When the film is evaluated for soil decomposition according to the conditions specified in ASTM D5988-18, the relative biodegradability is 90% or more within 24 months.

[0071] Furthermore, the biodegradable resin composition The film has an intrinsic viscosity of 1.0 dL / g or more, and exhibits an intrinsic viscosity loss of 10% or more, preferably 18% or more, after treatment at 70° C. and 85% RH for 6 hours.

[0072] Furthermore, the biodegradable resin composition The film has an intrinsic viscosity loss of 10% or less, preferably 6% or less, after treatment at 50° C. and 85% RH for 6 hours.

[0073] The present inventors have found that the biodegradable resin obtained by uniaxial or biaxial stretching composition It has been found that further treating the film at 120 to 150°C for 0.1 to 5 minutes is extremely advantageous in achieving the effect that the intrinsic viscosity loss rate after treatment for 6 hours at 70°C and 85% RH is 10% or more (preferably 25% or more) and the intrinsic viscosity loss rate after treatment for 6 hours at 50°C and 85% RH is 10% or less (preferably 6% or less).

[0074] The present invention further relates to the biodegradable resin. composition The present invention provides a multilayer film comprising a film. The multilayer film is a film having two or more layers. Different layers may have different functions, so the multilayer film can meet a wider variety of needs than a monolayer film.

[0075] The thickness of the multilayer film is not particularly limited, but is generally from 1 μm to 5 mm.

[0076] Furthermore, the multilayer film according to the present invention includes at least one layer selected from the group consisting of a vapor deposition layer, a heat seal layer, an adhesive layer, and an adhesive layer.

[0077] The vapor deposition layer is formed from at least one vapor deposition material selected from the group consisting of metals, metal oxides, and silica. The presence of such a vapor deposition layer can suppress the permeation of gases such as moisture, oxygen, and carbon dioxide, and can improve the barrier properties, mechanical properties, and appearance of the base film.

[0078] The heat seal layer is made of a thermoplastic or thermosetting resin. composition The film layer is a film layer containing the biodegradable resin according to the present invention, and the film layer is connected to the opposing film layer by melting and solidifying under relatively low heat and pressure conditions to form a sealed structure. composition It may have the same components as the film, or it may be different.

[0079] The adhesive layer is a solid, semi-solid or liquid layered material containing an adhesive that can be easily re-separated after adhesion, such as an acrylate-based, rubber-based or polyurethane-based adhesive, and serves to connect different layers in a multilayer film or to connect a multilayer film to another article.

[0080] The adhesive layer is a layered material in a solid, semi-solid or liquid state that can be cured by heating or other methods, and differs from the above-mentioned pressure-sensitive adhesive layer in that it cannot be easily separated after adhesion and curing. The adhesive layer includes one or more of a curable adhesive, a thermosetting resin, and a thermoplastic resin, and is intended to connect different layers in a multilayer film.

[0081] Furthermore, the multilayer film according to the present invention has a water vapor permeability coefficient of 10 g μm / m to provide better barrier properties. 2 less than 5 g μm / m 2 The following is the result.

[0082] Furthermore, the multilayer film according to the present invention has an oxygen permeability coefficient of 1000 cc μm / m in order to provide better barrier properties. 2 less than 500cc·μm / m 2 The following is the result.

[0083] The present invention further relates to the biodegradable resin. composition The present invention provides a film for packaging materials using the film.

[0084] The present invention further relates to the biodegradable resin. composition Provided is an adhesive tape using a film.

[0085] The present invention further provides a packaging film using the above multilayer film.

[0086] The present invention further provides an adhesive tape using the above multilayer film.

[0087] The biodegradable resin according to the present invention composition , the biodegradable resin composition and a multi-layer film using the biodegradable resin. composition Products made from the film, such as packaging films and adhesive tapes, combine rapid biodegradability with storage stability, and also have good mechanical, optical and barrier properties, making them suitable for a wide range of uses, including packaging and home delivery transportation. After their lifespan ends, they are rapidly biodegraded into small molecules such as carbon dioxide and water, and do not pollute the environment. EXAMPLES

[0088] Specific examples of the present invention are given below. , reference example The present invention will be described in more detail with reference to the following examples and comparative examples, but the scope of the present invention is not limited to the following examples.

[0089] Working Example , reference example The materials used in the examples and comparative examples are as follows. A1: Polylactic acid, manufactured by Natureworks, USA, specification: 4032D, number average molecular weight 110,000, biomass material, optical purity: 98%. A2: Polylactic acid, manufactured by Natureworks, USA, specification: 4060D, number average molecular weight 110,000, biomass material, optical purity: 78%. B1: Sebacic acid, manufactured by China National Pharmaceutical Reagent Co., Ltd., specification: AR, biomass material. B2: Adipic acid, manufactured by China National Pharmaceutical Reagent Co., Ltd., specification: AR, non-biomass material. B3: Glutaric anhydride, manufactured by China National Pharmaceutical Reagent Co., Ltd., specification: AR, non-biomass material. B4: Ammonium sebacate, manufactured by China National Pharmaceutical Reagent Co., Ltd., specification: AR, biomass material. C1: Polycaprolactone (PCL), manufactured by Ingevity, USA, specification: Capa 6500D, number average molecular weight 70,000, non-biomass material. C2: Polybutylene succinate (PBS), manufactured by Blue Ridge Tunhe Co., Ltd., China, specification: TH803S, number average molecular weight 50,000, non-biomass material. C3: Poly 3-hydroxybutyrate (P3HB), manufactured by Ningbo Tianan Co., Ltd., specification: Y3000, biomass material. D1: Zinc stearate, manufactured by Aladdin Reagents Co., Ltd., China, specification: AR, non-biomass material. D2: Calcium citrate, manufactured by China National Pharmaceutical Reagent Co., Ltd., specification: AR, biomass material. E1: Epoxy compound, manufactured by BASF, Germany, specification: Joncryl ADR 4468, non-biomass material. E2: Styrene-acrylonitrile-glycidyl methacrylate ternary random copolymer (SAG-008), manufactured by Fine-Blend Co., Ltd., China, specification: Fine-blend SAG-008, non-biomass material.

[0090] Working Example , reference example The raw materials and samples used in the comparative examples were measured according to the following experimental methods. The test temperature was 23°C unless otherwise specified.

[0091] Intrinsic viscosity (IV): A sample was dissolved in chloroform, and insoluble matter was removed by suction filtration using a sand core funnel with a pore size of 2 to 5 μm. A chloroform solution with a solute content of 3 ± 1 mg / mL was then prepared, and the effluent time T of the sample solution was measured at 30°C using an Ubbelohde viscometer with a capillary diameter of 0.3 to 0.4 mm. Separately, the effluent time To of pure chloroform was measured under the same conditions, and the intrinsic viscosity was calculated using the following formula. IV = [ln(T / To)] / c

[0092] Intrinsic viscosity loss rate: The sample was placed in an Espec PL-2J thermohygrostat and subjected to moist heat treatment. The moist heat treatment conditions were 70°C, 85% RH, 6 hours, or 50°C, 85% RH, 6 hours. Using the above method, the intrinsic viscosity (IV1) of the sample before moist heat treatment and the intrinsic viscosity (IV2) of the sample after moist heat treatment were measured. The intrinsic viscosity loss rate (ΔIV%) was calculated using the following formula. ΔIV%=(IV1-IV2) / IV1×100%

[0093] Carboxyl group content: A sample with mass M was dissolved in chloroform, and two drops of 0.1% by weight cresol red ethanol solution were added. Calibration was performed with a KOH standard solution of molar concentration N. The end point was the time when the solution changed from yellow to brown and did not fade within 15 seconds, and the volume of the KOH standard solution used was recorded as V. Separately, the same volume of chloroform was used, and two drops of 0.1% by weight cresol red ethanol solution were added. Calibration was performed with a KOH standard solution of molar concentration N. The end point was the time when the solution changed from yellow to brown and did not fade within 15 seconds, and the volume of the KOH standard solution used was recorded as V0. The carboxyl group content was calculated according to the following formula. Carboxyl group content = (V-V0) x N / M

[0094] Number average molecular weight: Measured using Agilent 1260 gel permeation chromatography (GPC), using dichloromethane as the mobile phase, and measuring three times to obtain the average value.

[0095] Optical purity: Polylactic acid was extracted from the sample, and measured six times using a SAC-i type fully automatic polarimeter manufactured by ATAGO Co., Ltd. of Japan, with dichloromethane as the solvent, and the average value of the specific rotation of polylactic acid in the extracted sample was taken. The optical purity was calculated using the following formula. Here, the specific rotation of the PLLA standard product is -156°. Optical purity = 100% x average specific rotation of sample / specific rotation of PLLA standard

[0096] Biomass degree: According to the components of the sample, the weight part of the organic matter of biological origin in the component was defined as M, and the weight part of the organic matter of non-biological origin in the component was defined as N. The biomass degree was calculated according to the following formula. Biomass ratio = M / (M+N) x 100%

[0097] Degradability in home composting: Biodegradability was evaluated by setting the compost temperature at 28±2°C and other conditions in accordance with ASTM D5338-15. If the relative biodegradability rate was 90% or more within 12 months, it was deemed to be degradable in home composting and was marked as "Good." If not, it was deemed to be degradable in home composting and was marked as "Poor."

[0098] Degradability in soil: Biodegradability was evaluated according to the conditions specified in ASTM D5988-18. If the relative biodegradability was 90% or more within 24 months, it was deemed to be degradable in soil and marked as "Good." If not, it was deemed to be non-degradable in soil and marked as "Poor."

[0099] Orientation degree: A 5 cm x 5 cm sample was used, and the cross section of the sample film was subjected to polarized Raman spectrum measurement in polarized mode using a Raman spectrometer manufactured by Horiba Corporation, Japan. -1 (The peak value is denoted as P) and 1769 cm -1 The peak at (peak value is indicated as Q) was measured and taken as a characteristic peak. P and Q were obtained in the machine direction (MD), transverse direction (TD) and thickness direction (ZD) of the film. The P / Q values ​​in the three directions were calculated, and (P / Q) MD , (P / Q) TD , (P / Q) ZD And then (P / Q)MD / (P / Q) ZD and (P / Q) TD / (P / Q) ZD The value was calculated. The measurement was repeated five times using the above method, and in each measurement, the measurement points were separated by 200 μm and the direction of the measurement points was random. (P / Q) MD / (P / Q) ZD and (P / Q) TD / (P / Q) ZD The average value of (P / Q) was calculated. MD / (P / Q) ZD and (P / Q) TD / (P / Q) ZD The average values ​​of these were recorded as the MD orientation degree and the TD orientation degree, respectively.

[0100] Melting enthalpy of polylactic acid and cold crystallization temperature in the second heating: Using a TA DSC Q100 type differential scanning calorimeter, the temperature was raised from 0°C to 215°C at a rate of 10°C / min (first heating process) and held at 215°C for 3 minutes. The temperature was lowered to 0°C at a rate of 10°C / min and held at 0°C for 3 minutes. The temperature was raised to 215°C at a heating rate of 10°C / min (second heating process), and the melting peak with a peak value temperature of 130 to 180°C in the second heating process was measured as the melting enthalpy of polylactic acid, and the peak value temperature of the heat dissipation peak in the second heating process was taken as the cold crystallization temperature in the second heating process.

[0101] Average diameter d and aspect ratio of the dispersed phase: The sample was stained with RuO4, ultra-thinly sliced ​​along the observation direction, and the cross section was observed with a JEOL2010 transmission electron microscope (TEM) manufactured by JEOL. composition The observation direction of the film was arbitrary. The observation direction of the film was the MD / ZD surface and the TD / ZD surface. Five photographs were taken at random at different positions of the sample at a magnification of 5000 times, and the outline of the dispersed phase was drawn with a pen. The area S of each dispersed phase and the length L of the two most distant points on the outline were calculated using the image processing software ImageJ 1.46r. Furthermore, the diameter d of each dispersed phase (the diameter of a circle whose area is equal to that of the dispersed phase was taken as this diameter d) was calculated using the following formula.

number

[0102] Thickness and thickness variation coefficient: Using a Sanyo Keiki 7050 thickness gauge, 9 evenly spaced locations were selected from the sample, the thickness of each location was measured, and the average value was taken as the sample thickness. Furthermore, the thickness variation coefficient was calculated using the following formula. Thickness variation coefficient = Thickness standard deviation / thickness × 100%

[0103] Transparency: A 5cm x 5cm sample was measured for haze and light transmittance using a haze meter HZ-V3 manufactured by SUGA Corporation of Japan with D65 as the light source. A 3cm x 5cm sample was placed in a cell containing 95% analytical grade pure ethanol, and the measured haze with D65 as the light source was taken as the internal haze.

[0104] Surface roughness: For a sample of 5 cm x 5 cm, the arithmetic mean surface height Sa was measured as the surface roughness using a non-contact surface measuring instrument VertScan-R5300 manufactured by Ryoka Corporation of Japan.

[0105] Tensile strength, elongation at break, tensile modulus: Test pieces with dimensions of 150 mm x 10 mm were prepared using a DUMBBELL SD-100 test piece preparation machine. The tensile strength and elongation at break of the test pieces were measured using a tensile testing machine AG-IS 1KN manufactured by Shimadzu Corporation, Japan. The gripping distance was 50 mm, and the tensile speed was 100 mm / min. The measurements were repeated five times.

[0106] Metal element content: The total content of sodium, magnesium, aluminum, potassium, calcium, barium, zinc, iron, copper, and tin metal elements was measured using an inductively coupled plasma optical emission spectrometer Icap7600 from Thermo Fisher Scientific, USA.

[0107] Water vapor transmission coefficient (WVP): For a sample of thickness T, the water vapor transmission coefficient (WVTR) was measured in a measurement environment of 38°C and 90% RH using a 3 / 34G water vapor transmission rate meter manufactured by AMETEK MOCON, USA, according to the standard ASTM F1249-13. The water vapor transmission coefficient was measured according to the following formula. WVP=T×WVTR

[0108] Oxygen permeability (OTP): For a sample of thickness T, the oxygen permeability (OTR) was measured in a measurement environment of 20°C and 0% RH using a 2 / 22H oxygen permeability meter manufactured by AMETEK MOCON, USA, according to the standard ASTM D3985-17. The oxygen permeability was measured according to the following formula. OTP=T×OTR Working Example 2~10,12~20, Reference examples 1~3 and Comparative Examples 1 to 4

[0109] The raw materials were mixed at 180°C and 100 rpm for 6 minutes using a TOYOSEIKI C4150-01 mixer to obtain a biodegradable resin containing the components shown in Tables 1 and 2. composition was manufactured.

[0110] Next, a biodegradable resin was molded using a TOYOSEIKI MINI TEST PRESS type molding machine. composition The mixture was molded at 180°C, quenched in ice water to prepare a molded product with a thickness of 200 μm. The molded product was then simultaneously biaxially stretched 3×3 at 80°C and a tensile speed of 5% / s using a Bruckner KARO-IV biaxial stretching machine, and then heat-treated at 140°C for 10 seconds to obtain a biodegradable resin. composition The film was produced.

[0111] Each embodiment, Reference example, Biodegradable resin in comparative examples composition The results of the characteristic measurements are shown in Tables 1 and 2. Reference example, Biodegradable resin in comparative examples composition The results of the measurement of the properties of the film are shown in Tables 3 and 4. , reference exampleThe intrinsic viscosity of the film, the intrinsic viscosity loss rate after 6 hours of treatment at 70°C and 85% RH, the intrinsic viscosity loss rate after 6 hours of treatment at 50°C and 85% RH, the carboxyl group content, the number average molecular weight, the optical purity, the biomass degree, the degradability by home composting, the degradability by soil composting, the melting enthalpy of polylactic acid, the cold crystallization temperature at the second heating, and the metal element content are composition The characteristic measurement results are substantially the same as those of the corresponding examples. , reference example In the measurements of the average diameter and aspect ratio of the dispersed phase in the MD / ZD plane of the film, the results are substantially the same as those in the TD / ZD plane.

[0112] The biodegradable resin in each embodiment composition If necessary, one or more functional layers such as a vapor deposition layer, heat seal layer, adhesive layer, or bonding layer can be added to the film. The water vapor permeability coefficient is 10g μm / m 2 Less than 5g μm / m 2 The oxygen permeability coefficient is 1000cc·μm / m 2 Less than 500cc μm / m 2 The deposition layers can be designed so that:

[0113] Therefore, the biodegradable resin according to the present invention composition The biodegradable resin according to the present invention has both rapid biodegradability and storage stability, and has a high biomass content. composition The film has a uniform thickness, high mechanical properties, excellent transparency, and a smooth surface.

[0114] [Table 1-1]

[0115] [Table 1-2]

[0116] [Table 2-1]

[0117]

Table 2-2

[0118]

Table 3

[0119]

Table 4

Claims

1. A biodegradable resin composition comprising 80% by weight or more of polylactic acid, one or more carboxylic acids selected from the group consisting of succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, cyclohexanecarboxylic acid, benzoic acid, and naphthalenecarboxylic acid, and / or 0.1 to 2% by weight of one or more carboxylic acid anhydrides selected from the group consisting of succinic anhydride, glutaric anhydride, benzoic anhydride, maleic anhydride, phenoxyacetic anhydride, phthalic anhydride, polysebacic anhydride, and maleic anhydride-containing polymers, and a compound containing an epoxy functional group, the composition having an intrinsic viscosity of 1.0 dL / g or more, an intrinsic viscosity loss rate after treatment for 6 hours at 70°C and 85% RH of 10% or more, and an intrinsic viscosity loss rate after treatment for 6 hours at 50°C and 85% RH of 10% or less, wherein the optical purity of the polylactic acid is 86 to 98%.

2. The composition contains 80% by weight or more of polylactic acid, 0.1 to 2% by weight of one or more carboxylic acids selected from succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, cyclohexane carboxylic acid, benzoic acid, and naphthalene carboxylic acid, and / or 0.1 to 2% by weight of one or more carboxylic acid anhydrides selected from succinic anhydride, glutaric anhydride, benzoic anhydride, maleic anhydride, phenoxyacetic anhydride, phthalic anhydride, polysebacic anhydride, and maleic anhydride-containing polymers, and a compound containing an epoxy functional group, and satisfies ASTM A biodegradable resin composition characterized in that, when decomposition is evaluated by home composting at 28°C according to the conditions specified in D5338-15, the relative biodegradability is 90% or more within 12 months, and the intrinsic viscosity loss rate after treatment for 6 hours at 50°C and 85% RH is 10% or less, wherein the optical purity of the polylactic acid is 86 to 98%.

3. 3. The biodegradable resin composition according to claim 2, wherein the intrinsic viscosity is 1.0 dL / g or more.

4. 3. The biodegradable resin composition according to claim 1, which has an intrinsic viscosity loss rate of 18% or more after treatment at 70° C. and 85% RH for 6 hours.

5. 3. The biodegradable resin composition according to claim 1, which has an intrinsic viscosity loss of 6% or less after treatment at 50° C. and 85% RH for 6 hours.

6. 0.1 x 10 -4 3. The biodegradable resin composition according to claim 1, which contains carboxyl groups in an amount of mol / g or more.

7. 0.1 x 10 -4 ~10x10 -4 7. The biodegradable resin composition according to claim 6, which contains mol / g of carboxyl groups.

8. 3. The biodegradable resin composition according to claim 1, wherein the polylactic acid has a number average molecular weight of 50,000 or more.

9. 3. The biodegradable resin composition according to claim 1, wherein the polylactic acid has a melting enthalpy of 10 to 58 J / g.

10. 10. The biodegradable resin composition according to claim 9, wherein the polylactic acid has a melting enthalpy of 20 to 35 J / g.

11. 3. The biodegradable resin composition according to claim 1, wherein the cold crystallization temperature in the second heating step is between 120°C and 135°C.

12. The biodegradable resin composition according to claim 1 or 2, characterized in that it contains 5 to 50% by weight of one or more of polycaprolactone, polybutylene succinate, polybutylene succinate adipate, polybutylene terephthalate adipate, polyhydroxyalkanoate, polypropylene carbonate, polyglycolic acid, or copolymers or derivatives of these polymers.

13. 3. The biodegradable resin composition according to claim 1, which contains 50 to 500 ppm of a metal element.

14. 14. The biodegradable resin composition according to claim 13, wherein the metal element is one or more of sodium, magnesium, aluminum, potassium, calcium, barium, zinc, iron, copper, and tin.

15. 3. The biodegradable resin composition according to claim 1, further comprising a dispersed phase, the dispersed phase having an average particle size of 0.5 to 6.0 μm.

16. The biodegradable resin composition according to claim 1, characterized in that, when decomposition is evaluated by home composting at 28°C according to the conditions specified in ASTM D5338-15, the relative biodegradability is 90% or more within 12 months.

17. The biodegradable resin composition according to claim 1 or 2, characterized in that, when soil decomposition is evaluated according to the conditions specified in ASTM D5988-18, the relative biodegradability is 90% or more within 24 months.

18. A biodegradable resin composition film comprising the biodegradable resin composition according to any one of claims 1 to 17.

19. The biodegradable resin composition film according to claim 18, characterized in that it is oriented in at least one of the MD and TD directions.

20. 20. The biodegradable resin composition film according to claim 19, characterized in that the degree of orientation in MD / ZD and / or TD / ZD is 170% or more.

21. 19. The biodegradable resin composition film according to claim 18, characterized in that it has a total light transmittance of 90% or more, a haze of 40% or less, and an internal haze of 8% or less.

22. 22. The biodegradable resin composition film according to claim 21, having a haze of 10% or less and an internal haze of 5% or less.

23. 19. The biodegradable resin composition film according to claim 18, characterized in that it contains a dispersed phase, and the aspect ratio of the dispersed phase in the MD / ZD plane and / or the TD / ZD plane is 1.5 or more.

24. The biodegradable resin composition film according to claim 18, characterized in that the roughness of at least one surface is 0.05 to 0.5 μm.

25. 19. The biodegradable resin composition film according to claim 18, characterized in that the thickness variation coefficient is 10% or less.

26. 19. The biodegradable resin composition film according to claim 18, characterized in that it has a tensile strength of 60 MPa or more, a breaking elongation of 20% or more, and a tensile modulus of elasticity of 4,500 MPa or less.

27. 27. The biodegradable resin composition film according to claim 26, characterized in that the breaking elongation is 100% or more and the tensile modulus is 3000 MPa or less.

28. A multilayer film comprising the biodegradable resin composition film according to any one of claims 18 to 27.

29. A packaging film using the biodegradable resin composition film according to any one of claims 18 to 27.

30. An adhesive tape using the biodegradable resin composition film according to any one of claims 18 to 27.

31. A packaging film using the multilayer film according to claim 28.

32. An adhesive tape using the multilayer film according to claim 28.

Citation Information

Patent Citations

  • Polylactate resin composition with controlled degradability and method for degradation

    JP2002256142A

  • Biodegradable resin crosslinked foam sheet and pressure- sensitive adhesive tape

    JP2003313344A

  • Polylactic acid fiber, and fiber structure

    JP2010150711A

  • Biodegradable resin composition

    JP2012149273A

  • Runner stop

    JP2012205506A